1993
DOI: 10.1071/ar9930215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term grain feeding on bovine body-fat colour: a cautionary note

Abstract: Seventeen Brahman steers were removed from pasture and fed a high grain diet for 8 weeks prior to slaughter. Carotenoid concentrations were determined in samples of serum and subcutaneous fat obtained either from live animals or at slaughter. At slaughter carcass fat colour was assessed according to AUS-MEAT specification. The concentrations of G-carotene in the serum of these animals fell rapidly (over 60%, P lt; 0.001) in the first 2 weeks on the grain diet and then plateaued. There was no change in either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
2
4
2
3
Order By: Relevance
“…In cattle, β-carotene is the main carotenoid absorbed from the intestine (Yang et al, 1993). Muscle β-carotene content was not different among dietary treatments in the present study (Table 3), in agreement with Mahecha et al (2009) and as expected from observed plasma β-carotene concentration.…”
Section: Accepted Manuscriptsupporting
confidence: 94%
“…In cattle, β-carotene is the main carotenoid absorbed from the intestine (Yang et al, 1993). Muscle β-carotene content was not different among dietary treatments in the present study (Table 3), in agreement with Mahecha et al (2009) and as expected from observed plasma β-carotene concentration.…”
Section: Accepted Manuscriptsupporting
confidence: 94%
“…The changes in the carotenoid concentration in the fat were similar to those found by Forrest (1981) but contrast with those found by Seiner et al (1992) and Strachan et al (1993), who found fat carotenoid concentration decreased for 97-105 days in steers fed low carotenoid diets. In contrast to these results, Yang et al (1993) found no decreases in the carotenoid concentration in subcutaneous fat or the objectively measured fat colour in steers fed a low carotenoid diet for 56 days, despite the serum carotenoid concentration decreasing to 0.4 291 Carotenoid concentrations in plasma and fat, and fat colour in the cattle in Experiments 1-3, were higher than reported by Australian workers. They found blood carotenoid concentrations of 2.3-2.6 ug/ml in cattle entering their feedlots (Yang et al 1992;Yang et al 1993;Seiner et al 1992;Strachan et al 1993) compared with 7.4 ± 0.4 ug/ ml for cattle in Experiment 3.…”
Section: Fat Carotenoid Concentrationscontrasting
confidence: 55%
“…In contrast to these results, Yang et al (1993) found no decreases in the carotenoid concentration in subcutaneous fat or the objectively measured fat colour in steers fed a low carotenoid diet for 56 days, despite the serum carotenoid concentration decreasing to 0.4 291 Carotenoid concentrations in plasma and fat, and fat colour in the cattle in Experiments 1-3, were higher than reported by Australian workers. They found blood carotenoid concentrations of 2.3-2.6 ug/ml in cattle entering their feedlots (Yang et al 1992;Yang et al 1993;Seiner et al 1992;Strachan et al 1993) compared with 7.4 ± 0.4 ug/ ml for cattle in Experiment 3. However, at the end of the feedlot period their cattle had blood carotenoid concentrations of 0.1-0.8 ng/ml which were similar to the concentration in Experiment 3.…”
Section: Fat Carotenoid Concentrationscontrasting
confidence: 55%
“…1,3,4 Yellow fat pigmentation in cattle ünished on pasture represents an important economic loss for the producer, because of the downgrading or even rejection of the resulting carcasses ; despite this, there is little information available on the mechanisms that cause this problem and the metabolic processes that the absorbed bC undergoes.5 b-carotene is the major carotenoid detected in the serum and adipose tissue of cattle ; it accounts for 85-90% of the colour in beef fat and the intensity of the colour is primarily correlated (r \ 0.92) with its carotenoid content and secondarily with lutein (LU) content. 5,6 There is also little information on the microbial transformation and metabolism of bC in the rumen.…”
Section: Introductionmentioning
confidence: 98%